Enhanced Framework for the Construction of Photonic Crystal Fiber Based Quantum Communication System - Rahman, Md. Mijanur (2009)
Quantum communication has been an important aspect of the envisioned quantum network consisting of quantum nodes and communication channels. It involves a number of disciplines including Quantum Optics and Quantum Information. The overall framework of quantum communication involves transmit and receive nodes, and a transmission medium for the transport of photon qubit.